Level of pancreatic division and postoperative pancreatic fistula after distal pancreatectomy: A retrospective case-control study of 157 patients with non-pancreatic ductal adenocarcinoma lesions. (May 2019) - Silvestri, Marta; Coignac, Antoine; Delicque, Julien; Herrero, Astrid; Borie, Fréderic; Guiu, Boris; Fabre, Jean-Michel; Souche, Regis
Abstract: Background: Several studies have suggested that the level of pancreatic division during distal pancreatectomy (DP) has an impact on postoperative pancreatic fistula (POPF) occurrence. The purpose of this study was thus to investigate the level of pancreatic division as a potential risk factor for POPF after DP for non-pancreatic ductal adenocarcinoma lesions (non-PDAC) in the era of parenchyma-sparing resection. Methods: Data from 217 patients requiring DP were collected in a prospectively maintained database from January 1997 to December 2017 and analyzed retrospectively. Only data from patients who underwent DP using a linear stapler for non-PDAC lesions were analyzed. The outcomes of DP with body/tail division (Body-Tail group) were compared to DP with neck division (Neck group). The primary outcome was POPF according to the 2016 ISGPF. Results: Data from 157 patients who underwent DP using a linear stapler for non-PDAC lesions were included for analysis. Body-Tail (n = 53) and Neck (n = 104) groups were comparable concerning demographic data, period of treatment, BMI, ASA score, comorbidities, type of lesion, median lesion size, laparoscopic or open approach and spleen preservation rate. No differences were found in POPF (5.5 and 12.5%, p  = 0.388) and new-onset pancreatogenic diabetes mellitus (22.5 vs. 20%; p  = 0.439) in Body-Tail and Neck groups respectively. Conclusion: Clinically relevant POPF and postoperative diabetes do not appear to be affected by pancreatic division level. The intention to prevent POPF or pancreatogenic diabetes should not influence the decision on level of pancreatic division during DP. Highlights: Several studies have suggested that the body/tail level for pancreatic division is a risk factor for POPF. In the present study, the level of pancreatic division was not significantly associated to POPF. New-onset diabetes mellitus does not appear to be associated with pancreatic division level. The intention to prevent POPF or diabetes should not influence the surgeon's decision on pancreatic transection site.